2019
DOI: 10.1111/eos.12614
|View full text |Cite
|
Sign up to set email alerts
|

Duration and sequence of muscular activation in dentate individuals and complete denture wearers during simulation of activities of daily living

Abstract: Occlusal support may influence muscular function during complex motor tasks. This study evaluated the duration and sequence of muscular activation of masticatory (temporal, masseter), postural head/neck (sternocleidomastoid, trapezius), postural trunk (rectus abdominis, paravertebrals), and low extremity strength (rectus femoris, gastrocnemius) muscles during simulation of activities of daily living (ADL) in edentulous women wearing complete dentures (n = 10) and in dentate women (n = 10). Electromyographic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Previous studies indicated that histories of prior HF and/or diabetes are likely to cause physical deterioration, including general muscle weakness [32][33][34][35]. Rising from bed requires strength in the upper and lower limb muscles as well as the trunk muscles [36,37]. Therefore, in patients with prior HF and/or diabetes that may have reduced physical function, rising time showed a higher odds ratio for frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that histories of prior HF and/or diabetes are likely to cause physical deterioration, including general muscle weakness [32][33][34][35]. Rising from bed requires strength in the upper and lower limb muscles as well as the trunk muscles [36,37]. Therefore, in patients with prior HF and/or diabetes that may have reduced physical function, rising time showed a higher odds ratio for frailty.…”
Section: Discussionmentioning
confidence: 99%
“…All data were calculated as mean values of muscle activity during each motion. Electrodes were attached to the following locations [26][27][28][29][30]: (1) Rectus femoris (RF), (2) tibialis anterior (TA), (3) biceps femoris (BF), (4) gastrocnemius (GCM), ( 5) deltoid (DEL), (6) upper trapezius (UT), (7) middle trapezius (MT), and (8) erector spine lumbar (ESL).…”
Section: Muscle Activitymentioning
confidence: 99%
“…When combined, these vari ables provide a more comprehensive analysis of muscle activity during complex movements. [13][14][15][16] Since 1950s, this technology has been used to analyse jaw muscle activity. 11,12 In 2017, a systematic review analysing this topic was published.…”
Section: Introductionmentioning
confidence: 99%